2016
DOI: 10.18632/genesandcancer.113
|View full text |Cite
|
Sign up to set email alerts
|

Pathway analysis of bladder cancer genome-wide association study identifies novel pathways involved in bladder cancer development

Abstract: Genome-wide association studies (GWAS) are designed to identify individual regions associated with cancer risk, but only explain a small fraction of the inherited variability. Alternative approach analyzing genetic variants within biological pathways has been proposed to discover networks of susceptibility genes with additional effects. The gene set enrichment analysis (GSEA) may complement and expand traditional GWAS analysis to identify novel genes and pathways associated with bladder cancer risk. We selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…GWAS also identified variants in genes involved in many other pathways as well as in yet not-annotated pathways. A recent pathway analysis based on GWAS data further identified variants in 9 novel genes ( RAPGEF1 , SKP1 , HERPUD1 , CACNB2 , CACNA1C , CACNA1S , COL4A2 , SRC , and CACNA1C ) [ 44 ]. Functional analyses have also provided evidences of causality for GSTM1-null, NAT2-slow, APOBEC- rs1014971, CCNE1 -rs8102137, SLC14A1 -rs10775480, PSCA -rs2294008, UGT1A -rs1189203, and TP63 -rs35592567 [ 45–52 ].…”
Section: Discussionmentioning
confidence: 99%
“…GWAS also identified variants in genes involved in many other pathways as well as in yet not-annotated pathways. A recent pathway analysis based on GWAS data further identified variants in 9 novel genes ( RAPGEF1 , SKP1 , HERPUD1 , CACNB2 , CACNA1C , CACNA1S , COL4A2 , SRC , and CACNA1C ) [ 44 ]. Functional analyses have also provided evidences of causality for GSTM1-null, NAT2-slow, APOBEC- rs1014971, CCNE1 -rs8102137, SLC14A1 -rs10775480, PSCA -rs2294008, UGT1A -rs1189203, and TP63 -rs35592567 [ 45–52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previously published articles, CACNA1C was up-regulated in brain tumors, leukemia, breast cancer and other tumors [ 14 ]. Besides, variants of CACNA1C were associated with bladder cancer, endometrial cancer and breast cancer risk [ 15 , 32 , 33 ]. All of these indicated that CACNA1C could also be a prognostic predictor for patients with OC.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of CCNE1 is also observed in aggressive osteosarcoma 70 and also implicated in cisplatin resistance in bladder cancer 71 . Differential expression of CCNE1 is also observed in other cancers including non‐small cell lung cancer (NSCLC), 72 bladder, 73 breast 74 and hepatocellular carcinoma 75 …”
Section: Discussionmentioning
confidence: 99%